MICROFINANCE GOVERNANCE: A MULTITHEORETICAL APPROACH FOR ASCERTAINING THE WIDER STAKEHOLDER INFLUENCING FORCES - Ibrahim Kamal Abdul Rahman; Mohammad Delwar Hussain; Md. Suliman Hossin (Asian Academy of Management Journal, 2019)
Scholars argue that the agency theory has some limitations as the sustaining theory of governance. It is its inability to distinguish the wider stakeholder influencing forces effecting on organisations. This paper delivers a concise picture incorporating other management-based theories to supplement agency theory in distinguishing the wider stakeholder influencing forces as well as the consequential extended governance standard it creates. Yet, for developing the theory building approach it has reviewed and critically examined the existing literatures. Furthermore, a circumstance is built to assimilate four existing theories that supplement each other to distinguish the wider stakeholder influencing forces. Finally, further studies have been recommended to certify the approach with wide-ranging real life institutional settings.